Fiscal Deficits and Current Account Deficits - Kumhof, Michael; Laxton, Douglas (Washington, D.C. : International Monetary Fund, 2009)
The effectiveness of recent fiscal stimulus packages significantly depends on the assumption of non-Ricardian savings behavior. We show that, under the same assumption, fiscal deficits can have worrisome implications if they turn out to be permanent. First, if they occur in large countries they significantly raise the world real interest rate. Second, they cause a short run current account deterioration equal to around 50 percent of the fiscal deficit deterioration. Third, the longer run current account deterioration equals almost 75 percent for a large economy such as the United States, and almost 100 percent for a small open economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet